An Education- and Telephone-Based Intervention to Improve Follow-up to Vision Care in Patients With Diabetes: A Prospective, Single-Blinded, Randomized Trial. (March 2016) - Zangalli, Camila S.; Murchison, Ann P.; Hale, Nicole; Hark, Lisa A.; Pizzi, Laura T.; Dai, Yang; Leiby, Benjamin E.; Haller, Julia A.
The aim was to evaluate the effectiveness of a multipronged intervention on diabetic dilated fundus examination (DFE) adherence. In a prospective trial, 521 patients with diabetes who were due for follow-up DFEs were randomized to usual care or the intervention group. Usual care received a form letter reminder to schedule and an automated reminder phone call prior to their appointment. Intervention participants received an educational brochure about diabetic eye disease and a personalized letter reminder to schedule. A research assistant called intervention participants to help schedule the appointment, and they received a reminder letter and an automated phone call prior to the scheduled visit. Patients in the intervention group were significantly more likely to schedule (63% vs 40%; P < .0001) and complete their appointment (48% vs 30%; P < .0001) compared with usual care. A multipronged intervention, including an educational mailing and telephone assistance with scheduling an appointment, significantly improved diabetic DFE adherence.